PENGEMBANGAN BOOKLET BERBASIS QR CODE PADA MATERI PENGUKURAN PANJANG DENGAN SATUAN BAKU KELAS III-A SDN KETETANG 1 BANGKALAN - Haya Zahra; Mohammad Edy Nurtamam (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The purpose of this study is to develop a QR Code-based booklet on length measurement material with a valid, attractive, and effective standard unit of class III-A elementary school Ketetang 1. This research uses the 4D model development method (Define, Design, Development, Disseminate). The subjects of this study are 31 students in grade III-A elementary school Ketetang 1. This development research uses data collection techniques such as observation, interviews, questionnaires, and tests. The results of the study show that the QR Code-based booklet product developed has been declared valid, attractive, and effective. The validity of the product was assessed by several experts, namely material experts at 92.5%, learning design experts at 98.21%, teaching material experts at 92.5%. The three validation results are included in the